Development of a Reporter System to Explore MMEJ in the Context of Replacing Large Genomic Fragments - Yanik, Mert; Ponnam, Surya Prakash Goud; Wimmer, Tobias; Trimborn, Lennart; Müller, Carina; Gambert, Isabel; Ginsberg, Johanna; Janise, Annabella; Domicke, Janina; Wende, Wolfgang; Lorenz, Birgit; Stieger, Knut; et al. (My University, 2018)
Common genome-editing strategies are either based on non-homologous end joining (NHEJ) or, in the presence of a template DNA, based on homologous recombination with long (homology-directed repair [HDR]) or short (microhomology-mediated end joining [MMEJ]) homologous sequences. In the current study, we aim to develop a model system to test the activity of MMEJ after CRISPR/Cas9-mediated cleavage in cell culture. Following successful proof of concept in an episomally based reporter system, we tested template plasmids containing a promoter-less luciferase gene flanked by microhomologous sequences (mhs) of different length (5, 10, 15, 20, 30, and 50 bp) that are complementary to the mouse retinitis pigmentosa GTPase regulator (RPGR)-ORF15, which is under the control of a CMV promoter stably integrated into a HEK293 cell line. Luciferase signal appearance represented successful recombination events and was highest when the mhs were 5 bp long, while longer mhs revealed lower luciferase signal. In addition, presence of Csy4 RNase was shown to increase luciferase signaling. The luciferase reporter system is a valuable tool to study the input of the different DNA repair mechanisms in the replacement of large DNA sequences by mhs.
Keywords: ddc:610